1987
DOI: 10.1128/aac.31.11.1727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, NaCl, and methicillin on penicillin-binding proteins, growth, peptidoglycan synthesis, and autolysis in methicillin-resistant Staphylococcus aureus

Abstract: Methicillin-resistant Staphylococcus aureus strains produce a fifth penicillin-binding protein (PBP), PBP 2', with low affinity for I-lactam antibiotics that is believed to represent a P-lactam-insensitive peptidoglycan transpeptidase. In an effort to evaluate the adequacy of PBP 2' as an explanation of methicillin resistance, PBP 2' production and the responses of growth and peptidoglycan synthesis to methicillin under different environmental conditions have been compared. In the heterogeneous methicillin-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 29 publications
(32 reference statements)
2
54
0
1
Order By: Relevance
“…Previously, O'Brien et al (372) observed that mutagenized strains of MRSA defective for D-alanyl ester formation have increased methicillin resistance. These results correlated with the enhanced expression of methicillin resistance when MRSA is grown in either 7.5% NaCl or at pH 8, condi- (314,429). In studies of the mecA element in S. aureus, Jenni and Berger-Bächi (245) found that although mecA altered autolytic behavior, it had no effect on the cellular content, chain length, or D-alanine substitution of LTA and WTA.…”
Section: Correlation With Antibacterial Actionmentioning
confidence: 76%
“…Previously, O'Brien et al (372) observed that mutagenized strains of MRSA defective for D-alanyl ester formation have increased methicillin resistance. These results correlated with the enhanced expression of methicillin resistance when MRSA is grown in either 7.5% NaCl or at pH 8, condi- (314,429). In studies of the mecA element in S. aureus, Jenni and Berger-Bächi (245) found that although mecA altered autolytic behavior, it had no effect on the cellular content, chain length, or D-alanine substitution of LTA and WTA.…”
Section: Correlation With Antibacterial Actionmentioning
confidence: 76%
“…According to the 1996 national nosocomial infection surveillance in Korea, Staphylococcus aureus (17.2%) was the most commonly isolated organism, and 78.8% of S. aureus were methicillin-resistant (4). Since the phenotypic expression of methicillin-resistance is influenced by many factors-such as inoculum size, incubation time and temperature, pH of the medium, salt concentration of the medium, and exposure to -lactam antibiotics, the performance of susceptibility tests has been erratic (5,6). Moreover, methicillin-resistant staphylococci are also resistant to other antibiotics, including -lactams, aminoglycosides, and macrolides (7).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the activities of some murein hydrolases are mediated at the posttranslational level, including substrate modification, selective transport, interaction with lipoteichoic acids, etc. (5,10,25,45).…”
mentioning
confidence: 99%
“…Therefore, we predicted that Gcp may be involved in modulating autolysis of S. aureus. Bacterial autolysis plays important physiological roles in cell separation and ongoing peptidoglycan remodeling (6,25). It has been demonstrated that peptidoglycan (murein) hydrolases are involved in the lysis of bacteria by hydrolyzing either the glycan or the peptide moieties of peptidoglycan in the gram-positive cell wall (38).…”
mentioning
confidence: 99%